A case of cicatricial pemphigoid with esophageal involvement - , Selim NALBANT, Ergün SARAÇOĞLU, Necmettin KARAEREN, Sait BAĞCI, Can UYGURER, Celalettin ÇETİN, Kemal DAĞALP, Ahmet ALPER (Turkish Journal of Gastroenterology 1, 2019)
-